ARMADA: Assessing reliable measurement in Alzheimer's disease and cognitive aging project methods. Issue 8 (17th November 2021) - Weintraub, Sandra; Karpouzian‐Rogers, Tatiana; Peipert, John Devin; Nowinski, Cindy; Slotkin, Jerry; Wortman, Katy; Ho, Emily; Rogalski, Emily; Carlsson, Cynthia; Giordani, Bruno; Goldstein, Felicia; Lucas, John; et al.
Abstract: Introduction: Early detection of cognitive decline in older adults is a public health priority. Advancing Reliable Measurement in Alzheimer's Disease and Cognitive Aging (ARMADA), a multisite study, is validating cognition, emotion, motor, and sensory modules of the National Institutes of Health Toolbox for Assessment of Neurological and Behavioral Function (NIHTB) in the aging spectrum from cognitively normal to dementia of the Alzheimer's type (DAT). Methods: Participants 65 to 85 years old, in demographic groups racially proportional to the general US population, are recruited in one of three groups to validate the NIHTB: cognitively normal, amnestic mild cognitive impairment (aMCI), or mild DAT. Additional special emphasis cohorts include (1) Blacks in the three clinical groups; (2) Spanish‐speakers in the three clinical groups; (3) cognitively normal, population‐proportional, over age 85. Discussion: Longitudinal study will determine whether NIHTB can predict cognitive decline and is associated with Alzheimer's disease biomarkers. Here, we detail the methods for the ARMADA study.